PEMBUATAN BIODIESEL DARI BIJI KEMIRI SUNAN - Djeni Hendra (Jurnal Penelitian Hasil Hutan, 2014)
Due to limitation of resources the availability offossil fuel is become decreasing, an alternative fuel is needed such as Aleurites trisperma Blancoseed before of big potential as source for plantation, the composition of seed kernel hasa highlevel of oil (43.3%).Biodiesel production process was done in the laboratory, its objective to establish the optimum condition. The addition ofcatalyst H PO (degumming process) of 0,5%, 0,75%, 1%. The esterification treatment use a methanol catalyst mixtureof 10%, 15%, 20% with HCl and H SO of 0,5%, 0,75% and 1%. The transestrification treatment use a methanolcatalyst mixture of 10%, 15% and 20% with KOH and NaOH of 0,2%, 0,4%, 0,6%. Optimum results will beapllied to biodiesel production in large scale.In making Aleurites trisperma Blanco biodiesel which meet the Indonesian National Standard quality (SNI),chemical used were mixture of methanol 20% (v/v) and catalys NaOH 0.6% (w/v), where resulting in biodiesel withmoisture content 0.05 %, acid number 0.76 mg KOH/g, free fatty acid content 0.38 %, density 865 kg/m , kineticviscocity at 40 C of 5.41 mm /s (cSt), base number 101.49 mg KOH/g, alcyl ester content 104.55% massa, iodnumber 109.73 g I /100 g, cetana number 59,08, and yield of biodiesel oil 79.92 %.